2018
DOI: 10.1029/2018jc013965
|View full text |Cite
|
Sign up to set email alerts
|

The Density‐Driven Winter Intensification of the Ross Sea Circulation

Abstract: The circulation over the Ross Sea continental shelf facilitates the exchange between the Southern Ocean and the Ross Ice Shelf cavity. Here transport and mixing processes control the access of oceanic heat from the Southern Ocean to the ice shelf base, the formation of sea ice, and the production of High Salinity Shelf Water (HSSW) in polynyas and hence the subsequent formation of Antarctic Bottom Water. A climatological ocean‐ice shelf coupled model of the Ross Sea Sector including the cavity, with prescribed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
89
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 52 publications
(95 citation statements)
references
References 137 publications
(238 reference statements)
4
89
2
Order By: Relevance
“…In February, this strong barotropic flow under the ice shelf is substantially weaker. Jendersie et al () found a similar seasonality of the flow under the western ice shelf and attributed it to stronger horizontal density gradients driven by winter sea ice formation. North of the ice shelf, the shelf break jet (the Antarctic Slope Current) and intrusions onto the continental shelf are intensified.…”
Section: Resultsmentioning
confidence: 88%
“…In February, this strong barotropic flow under the ice shelf is substantially weaker. Jendersie et al () found a similar seasonality of the flow under the western ice shelf and attributed it to stronger horizontal density gradients driven by winter sea ice formation. North of the ice shelf, the shelf break jet (the Antarctic Slope Current) and intrusions onto the continental shelf are intensified.…”
Section: Resultsmentioning
confidence: 88%
“…The co-occurrence of higher frequencies of strong southerly wind events we observed in the RSP region over winter and the relatively rapid manifestation as thicker SPLs in McMurdo Sound in the following late spring of 2011 and 2017 also suggests a shorter time scale for HSSW and ISW ventilation from the deeper cavity than most modeling studies. Jendersie et al (2018) modeled the circulation within the McMurdo-Ross ice shelf cavity to be weakest from March to May before intensifying continuously until November and December. They attributed this to increased HSSW production in the RSP and resultant inflow to the cavity via McMurdo Sound/Haskell Strait and a channel east of Ross Island.…”
Section: Journal Of Geophysical Research: Oceansmentioning
confidence: 99%
“…The amount of basal melting depends on the heat content of the underlying ocean determined by the ocean circulation under the ice shelf, and the intensity of mixing near the ice base to maintain an upward flux of ocean heat against the stabilizing effect of buoyant meltwater production (Holland & Jenkins, 1999). For the Ross Ice Shelf, the sub-ice-shelf circulation is described in detail by Assmann et al (2003), Dinniman et al (2011Dinniman et al ( , 2016, Jendersie et al (2018), Tinto et al (2019), and others. The low basal melt rates, and possible marine ice accumulation, that we estimate under most of the ice shelf (Figure 7a) is consistent with previous satellite-derived estimates (Moholdt et al, 2014;Rignot et al, 2013).…”
Section: Causes Of Spatial Variability Of Melt Ratesmentioning
confidence: 99%